2019
DOI: 10.2174/1874944501912010541
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Profile of Injured Motorcyclists in Road Traffic Accident Treated in a Third-Level Hospital

Abstract: Background In Mexico, motorcycle use is increasingly prevalent owing to the availability and low fuel consumption of the vehicle. With the increasing number of motorcycle users, the rate of injuries and mortality due to road traffic accidents has also increased. Objective The study aimed to describe the epidemiological profile of injured motorcyclists treated in a third-level hospital, who were involved in traffic accidents in Guadalajara's Metropolitan Area and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In another study, the characteristics of associated risk and severe injuries were "improper functioning of the motorcycle before the accident", "traffic infraction by drivers". In contrast, the characteristic that reduces the risk is "the motorcycle brand" (Méndez-Magaña et al, 2019). Due to constraints of the Emergency Service Provider, death rate and its spatial distribution could not be analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, the characteristics of associated risk and severe injuries were "improper functioning of the motorcycle before the accident", "traffic infraction by drivers". In contrast, the characteristic that reduces the risk is "the motorcycle brand" (Méndez-Magaña et al, 2019). Due to constraints of the Emergency Service Provider, death rate and its spatial distribution could not be analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Motorcycle popularization and affordability has increased in the last years, and acquisition focus and use purposes of small or big engine potency differs both in user profile and in marketing (Marim, 2010). It is believed and demonstrated that motorcycles with bigger engine potency can present differences in accident profile compared to small engine potency (Langley et al, 2000;Waseem et al, 2019;Hidalgo-Fuentes & Sospedra-Baeza, 2019;Méndez-Magaña et al, 2019), which can provide subsidies for specific health policies.…”
Section: Introductionmentioning
confidence: 99%